2009
DOI: 10.1007/s00246-009-9510-6
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Elevated Systolic Blood Pressure and Hypercholesterolemia on Carotid Intima–Media Thickness in Children and Adolescents

Abstract: This study aimed to investigate the synergistic effects of elevated systolic blood pressure (SBP) and hypercholesterolemia on carotid intima-media thickness (cIMT). For this study, 60 children with hypercholesterolemia and 40 healthy control children were divided into four subgroups: hypercholesterolemic children with normal (<90th percentile) or elevated (>or= 90th percentile) SBP and control children with normal or elevated SBP. The highest mean and maximal cIMT values were found in the hypercholesterolemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…This is in accordance with other studies on weight and BMI development in children and adolescents with diabetes type 1 [23]. The BMI as mentioned above played a major role in cIMT development.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with other studies on weight and BMI development in children and adolescents with diabetes type 1 [23]. The BMI as mentioned above played a major role in cIMT development.…”
Section: Discussionsupporting
confidence: 92%
“…Even more impressive was the influence of the BMI z-score at first measurement, increasing the risk to develop a major augmentation in cIMT z-scores by the factor 3.02. As resulting from the literature, the association of several cardiovascular risk factors seems to add deleterious effects to the vascular bed in diabetic children [23]. Recently, also postprandial glucose levels have been found to be correlated to cIMT [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors such as dyslipidemia are well established in the physiopathological mechanism of atherosclerosis and associated to increased CIMT in patients with DM1 [29, 33] as we were able to show. In the diabetes control and complications trial/epidemiology of diabetes interventions and Complications study, LDL-C levels, formation of immune complexes, oxidized LDL levels, and final products of enzymatic glycosylation of LDL were significantly associated with the progression of CIMT [34].…”
Section: Discussionsupporting
confidence: 72%
“…A strong association has been reported between increased CIMT in patients with DM1 and high SBP, stronger than that with LDL-C levels, family history of CVD, and diabetes duration [29, 30]. It had been suggested that among metabolic syndrome components, SBP is one of the most significant factors associated with increased CIMT [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…В обзоре Американской ассоциации сердца (American Heart Association, AHA), одобренной Американской ака-демией педиатрии [22], подчеркивается, что наличие традиционных факторов риска атеросклероза в сочета-нии с хроническими воспалительными заболеваниями ассоциируется с ускоренным развитием атеросклероза и появлением клинических коронарных событий в дет-ском или молодом возрасте. Длительные популяционные исследования с использованием неинвазивных методов оценки функции эндотелия подтвердили связь структурных и функциональных изменений сосудов у детей и подрост-ков с клинически значимыми сердечно-сосудистыми забо-леваниями в последующие возрастные периоды [79][80][81].…”
Section: вопросы современной педиатрииunclassified